ISOLASI DAN IDENTIFIKASI SENYAWA TOKSIK PADA SPONS DARI PERAIRAN GILI SULAT-LOMBOK - I M. Dira Swantara; Agus Supriyono; Mila Trinoviani (Program Studi Kimia, FMIPA, Universitas Udayana (Program of Study in Chemistry, Faculty of Mathematics and Natural Sciences, Udayana University), Bali, Indonesia, 2007)
The isolation and identification of toxic compound on sponge from BPPT collection sub P3-TFM derivedfrom Gili Sulat, Lombok waters has been conducted. The extraction applied was maceration method, which wastotally conducted using three kinds of solvents namely, methanol, dichloromethane, and n-hexane. The total extractobtained was then partitioned into liquid using ethyl acetate and n-butane respectively. The most toxic extraction wasseparated by chromatography column with sephadex LH-20 as the stationary phase and methanol as the mobilephase. Identification of the active isolate was conducted by gas chromatography - mass spectroscopy with the aim ofWiley 275.L. database.Toxin test to sponge of BPPT collection sub P3-TFM showed that SL2 sponge was proved to be the mosttoxic one. The most toxic fraction of SL2 sponge at LC50 at 100 ppm was assumed to be the combination of 7compounds, namely benzene acetatic acid (8.9%), dioktil hexadioate (4.5%), bis (2etilheksil) 1.2-benzeneboksilat(53.1%), 2, 6, 10, 15, 19, 23 hexamethyl 2, 6, 10, 14, 18, 22-tetracosahexene, (17.1%), nonacosane (7.8%),cholesterol (3.8%) and eicosane (4.8%).